Pengaruh Pemberian Pestisida Nabati Daun Tembakau Terhadap Mortalitas Keong Mas (Pomacea canakuculaka) - Wulandari, Melisyah Putri; Rahmadani, St. (JUSTER : Jurnal Sains dan Terapan, 2024)
The results of the mortality percentage of golden snails (Pomacea canakuculaka L) show that it is said to be effective if it is more than 50%. Meanwhile, golden snail mortality is said to be ineffective below 50%. At a concentration of 50 gr it shows a mortality percentage of 70%, which means it is effective, while at a concentration of 100 gr it shows a mortality percentage of 76% and at a concentration of 150 gr it shows a mortality percentage of 83%, which means that at a concentration of 100 gr and 150 gr it is effective as a botanical pesticide for tobacco leaves. on mortality of golden snails (pomacea canakuculaka L.). Based on the results of research on the effect of using tobacco leaf botanical pesticides on the mortality of golden snails (Pomacea canakuculaka L.), it can be concluded that the greater the concentration of tobacco leaves used, the more effective the mortality of golden snails (Pomacea canakuculaka L.).